2020
DOI: 10.3390/molecules25081771
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Bond Lengths from Orbital-Free Density Functional Theory

Abstract: This work presents an investigation to model chemical bonding in various dimers based on the atomic fragment approach. The atomic fragment approach is an ab-initio, parameter-free implementation of orbital-free density functional theory which is based on the bifunctional formalism, i.e., it uses both the density and the Pauli potential as two separate variables. While providing the exact Kohn-Sham Pauli kinetic energy when the orbital-based Kohn-Sham data are used, the bifunctional formalism allows for approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…The first test case with c = 0 and d = 0 is the bare atomic fragment approach itself, in which case the equilibrium bond distances directly follow the size of the core shells, which decrease from Li to Ne and thus, yield a very short bond length in the case of Ne 2 [for a detailed explanation see Finzel (2021)]. The construction of a deformation potential with c = 2 and d = 0 means that one electron pair interacts constructively, while there are no destructive terms at all.…”
Section: Resultsmentioning
confidence: 99%
“…The first test case with c = 0 and d = 0 is the bare atomic fragment approach itself, in which case the equilibrium bond distances directly follow the size of the core shells, which decrease from Li to Ne and thus, yield a very short bond length in the case of Ne 2 [for a detailed explanation see Finzel (2021)]. The construction of a deformation potential with c = 2 and d = 0 means that one electron pair interacts constructively, while there are no destructive terms at all.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to previously published methods [ 53 , 54 ], energy minimization has been performed by optimization of the respective exponents for the valence region of the participating atoms, where the electron density is represented by atom-centered, squared, real-type nodeless Slater functions of 1S and 2S-type only Those nodeless spherical Slater functions are given by [ 70 , 71 ] with …”
Section: Methodsmentioning
confidence: 99%
“…In the applied formalism, the choice of atomic fragments markedly influences the ability of the method to properly model chemical bonding curves. It has been shown that artificially constructed closed-shell atoms better mimic the corresponding atomic fragments within the molecule, and thus yield better equilibrium bond lengths compared to experimental data [ 54 ] than the ordinary ground-state atoms. In the recently introduced OF-DFT methods, the total kinetic energy was given by employing the fragment Pauli kinetic energy given in terms of a bifunctional where the molecular Pauli potential is approximated by its atomic fragment variant and is the KS Pauli potential for atom A .…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations